A Study of r- and u-Magnitude Dependence in the Spatial Orientation of Spin Vectors of SDSS Galaxies having redshift 0.10 < z < 0.11 - Yadav, Shiv Narayan; Aryal, Binil (Himalayan Physics, 2015)
We present a study of spin vector orientations of 44749 r and u-magnitude SDSS (Sloan Digital Sky Survey) galaxies having redshift 0.10 to 0.11. The r and u-magnitudes are observed through 616.5 nm and 354.3 nm CCD (charge coupled device) filter attached to SDSS telescope located at New Mexico, USA. We have converted two dimensional data to three dimensional galaxy rotation axes. Our aim is to find out non-random effects in the spatial orientation of galaxies. In addition, we wanted to check r and u-magnitude dependence in the spatial orientation. The expected isotropy distribution curves are obtained by removing the selection effects and performing a random simulation method. In general, spin vector orientations of galaxies is found to be random, supporting Hierarchy model of galaxy formation. A local anisotropy is observed in few samples suggesting a gravitational tidal interaction between neighbor galaxies, a merging process in which the angular momentum vector distort the original alignment of evolution of rotational supported system to the randomized system. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014) Page: 1-11